Study On The Impact Biodiesel Onto Fuel Pump And Nozzle Wear In 5 Kva Generator Diesel Engine - Mardono Mardono; Maymuchar Maymuchar (Testing Center for Oil and Gas LEMIGAS, 2010)
One of diesel fuel functions is to lubricate fuel pump components. Wearing process on fuel pump causes fuel pressure to the combustion chamber will drop. The pump will not distribute the hydrocarbon well in to the combustion chamber, as result incomplete combution process will occur. The objective of this study is to observe the impact of biodiesel on fuel pump and injector of the diesel engine. A 5 KVA generator diesel engine was used in this study and was operated using 48 CN diesel fuel (â€œMinyak Solar 48â€) (B0), biodiesel 50%-volume (B50) and biodiesel 100% (B100). Each of which was subjected to 100 hour running operation and 1000 Watt load. The results of this research show that biodiesel have a positive impact in reducing wear occurence in the generator diesel engine fuel pump components or injector nozzle.